Is male rhesus macaque facial coloration under intrasexual selection? - Petersdorf, Megan (Behav Ecol, 2017)
Exaggerated male traits can evolve under intra- or intersexual selection, but it remains less clear how often both mechanisms act together on trait evolution. While the males of many anthropoid primate species exhibit colorful signals that appear to be badges of status under intrasexual selection, the red facial coloration of male rhesus macaques (Macaca mulatta) appears to have evolved primarily under intersexual selection and female mate choice. Nonetheless, experiments show that red color is salient to males, raising the question of whether the signal may also be under intrasexual selection. Here, we examine whether males express this signal more strongly in competitive contexts. Facial images were collected on all 15 adult males of a free-ranging social group during the peak of the mating season, and coloration was quantified using visual models. Results show that males more similar in facial redness were more likely to interact aggressively than more dissimilar ones, suggesting that color may be involved in the assessment of rivals. Furthermore, males exhibited darker coloration on days they were observed copulating, and dominance rank predicted facial redness only on copulating days, suggesting that coloration may also advertise motivation to defend a mate. Male rhesus macaque facial coloration may thus mediate agonistic interactions with rivals during competition over reproductive opportunities, such that it is under both inter- and intrasexual selection. However, color differences were small, raising perceptibility questions. It remains possible that color variation reflects differences in male condition, which in turn alter investment towards male–male competition and mating effort.